Sistem Informasi Truk PT Daisy Mutiara Samudra Berbasis Website - Renata Alvianita; Diva Tri Wulandari; Anita Aprilia Kartini; Mitha Azhari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Truck information systems are currently an important part of the logistics and transportation sector in Indonesia. Several important aspects such as technology are very helpful for knowing information about trucks in the current era of digitalization and refer to a period in which digital information technology played an important role in almost all aspects of human life. It is this information technology that has brought many benefits in the field of truck information system services, including increasing efficiency, reducing operational costs, and improving service quality. This Retruck website is designed to make it easier for customers to view information about the specifications and price range of the trucks they want to rent to facilitate the delivery process. This study aims to develop and implement a truck information system at PT Daisy Mutiara Samudra using web-based technology. The data collection method used is observation and literature study. The data collected was then analyzed using the Waterfall system development method. The result of this research is a truck information system that is integrated with PT Daisy Mutiara Samudra's website. This system can make it easier for customers to order trucks online. In addition, this system can also assist companies in managing information related to fleets, and makes it easier for customers to find out about trucks in a more complete, effective and efficient manner. With this truck information system, PT Daisy Mutiara Samudra can improve operational efficiency and provide better service to customers.